Unregulated toxic emissions from automotive diesel engines operating with potential neutral carbon diesel fuel substitutes (2023)
ABSTRACT : The global transportation sector is dominated by energy from fossil fuel sources, however, in the context of climatic change there is a growing need to shift towards renewable energy sources. In addition, this sector plays a leading role for the deteriorating air quality in urban areas which is a major risk to human health, and it is expected to be the highest source of air pollution in the foreseeable future. Climate change, energy security, containment of regulated emissions and environmental concerns are considered as the main driving forces behind alternative fuels research. Potential low and neutral carbon fuels produced from renewable resources seem to be a preferable class of fuels for internal combustion engines. Although it is recognized that the combustion of low and neutral carbon fuels still generates pollution, the levels of regulated emissions and the carbon footprint decreases compared to the use of fossil fuels. The best-known family of low and neutral carbon fuels are biodiesel, ethers, renewable diesel, bioalcohols, which have proved advantages as they are aromatic-free, sulfur-free and some of them can provide extra oxygen content. They have emerged as cleaner alternatives to mineral diesel and they can significantly reduce regulated emissions without compromising engine performance. However, several harmful volatile organic species which pose significant hazards to human health can be affected by using these low and neutral carbon fuels. This thesis studied the impact of a broad group of conventional and nonconventional biofuels on the formation of two groups of unregulated toxic emissions and in the induced biological risk in terms of cytotoxicity (cell death), genotoxicity (DNA damage), apoptosis (induced cell death) and ecotoxicity. Different methods were used to characterise the exhaust gases, both particles and gas phase, and a sampling system for unregulated toxic pollutants was designed and built. In the first part, unregulated emissions of carbonyl compounds and polycyclic aromatic hydrocarbons in solid particle and gaseous phase, the contribution to ozone formation potential and the biological response of soluble organic fraction and water-soluble fraction extracted from particulate matter were investigated. Tests were conducted in an automotive diesel engine fueled with butanol, pentanol and hydrotreated vegetable oil blended with diesel, operating under two stationary modes, representative of urban driving conditions from the worldwide light duty test cycle (WLTC). Results showed that independently of the engine operating mode, alcohols exhibited the highest carbonyl compound emissions and thus the highest ozone formation potential. Independently of the fuel and engine operating mode, most of the PAH were present in the gas-phase. It was observed that some local combustion conditions might increase the emissions of PAH for renewable fuels. Regarding the biological response, all PM samples exhibited genotoxic effects. However, none of them showed cytotoxicity nor ecotoxicity effects. Following the same sampling methodology, the second part investigated the unregulated emissions in both, gas and particle phases, from a Euro 6b diesel engine, operated with four unconventional and advanced biofuels blended with diesel fuel and hydrotreated vegetable oil as base biofuel. The engine was operated following the WLTC driving cycle, starting from cold-engine conditions. Gas phase samples were collected and analyzed at each one of the four phases of the driving cycle. In addition, the apoptotic index induced by gas and particle emissions was determined. Results showed that the total gaseous PAH and carbonyl emission factors were higher at the low-speed phase for all fuels. Gas-phase PAH emission factors exceeded particle-bound PAH. Carbonyl emission factors markedly exceeded gaseous PAH emissions. Although particle-bound PAH comprises only a small fraction of total PAH emissions, both phases (gas and particles) contributed approximately equal to the toxicity associated with carcinogenic PAH. The apoptotic cells percentage increased in a dose-dependent manner and it was significantly higher in cells exposed to gas phase-derived samples in comparison with particle phase. Finally, special care on unregulated emissions and biological risk is highly recommended when promoting low or zero carbon footprint fuels for internal combustion engines. Although the net carbon emissions could be drastically decreased, several harmful PAH and carbonyl compounds can be significantly increased and thus the risk to human health.